Cone Phosphodiesterase-6γ’ Subunit Augments Cone PDE6 Holoenzyme Assembly and Stability in a Mouse Model Lacking Both Rod and Cone PDE6 Catalytic Subunits - Deng, Wen-Tao; Kolandaivelu, Saravanan; Dinculescu, Astra; Li, Jie; Zhu, Ping; Chiodo, Vince A.; Ramamurthy, Visvanathan; Hauswirth, William W. (Frontiers in Molecular Neuroscience, 2018)
Rod and cone phosphodiesterase 6 (PDE6) are key effector enzymes of the vertebrate phototransduction pathway. Rod PDE6 consists of two catalytic subunits PDE6α and PDE6β and two identical inhibitory PDE6γ subunits, while cone PDE6 is composed of two identical PDE6α’ catalytic subunits and two identical cone-specific PDE6γ’ inhibitory subunits. Despite their prominent function in regulating cGMP levels and therefore rod and cone light response properties, it is not known how each subunit contributes to the functional differences between rods and cones. In this study, we generated an rd10/cpfl1 mouse model lacking rod PDE6β and cone PDE6α’ subunits. Both rod and cone photoreceptor cells are degenerated with age and all PDE6 subunits degrade in rd10/cpfl1 mice. We expressed cone PDE6α’ in both rods and cones of rd10/cpfl1 mice by AAV-mediated delivery driven by the ubiquitous, constitutive small chicken β-actin promoter. We show that expression of PDE6α’ rescues rod function in rd10/cpfl1 mice, and the restoration of rod light sensitivity is attained through restoration of endogenous rod PDE6γ and formation of a functional PDE6α’γ complex. However, improved photopic cone responses were achieved only after supplementation of both cone PDE6α’ and PDE6γ’ subunits but not by PDE6α’ treatment alone. We observed a two fold increase of PDE6α’ levels in the eyes injected with both PDE6α’ plus PDE6γ’ relative to eyes receiving PDE6α’ alone. Despite the presence of both PDE6γ’ and PDE6γ, the majority of PDE6α’ formed functional complexes with PDE6γ’, suggesting that PDE6α’ has a higher association affinity for PDE6γ’ than for PDE6γ. These results suggest that the presence of PDE6γ’ augments cone PDE6 assembly and enhances its stability. Our finding has important implication for gene therapy of PDE6α’-associated achromatopsia.